KINERJA PENYELENGGARAAN PELAYANAN IMB (IZIN MENDIRIKAN BANGUNAN) DI KECAMATAN LUBUK BASUNG PASCA GEMPA BUMI 30 SEPTEMBER 2009 - , ARIE KURNIA ARNOLD, SSTP, Dr. Agus Heruanto Hadna, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The 7.6 Richter Scale (RS) hit West Sumatera area on 30 September 2009 caused the 10,401 construction units of Lubuk Basung sub-district, Agam district in damaged and destroyed condition. In addition to financial problem, one of the obstacles that the community has encountered in the building reconstruction effort concerns with the complicated procedure of Izin Mendirikan Bangunan (IMB)/Building Development Permit that the Lubuk Basung sub-district government issues. This research aimed to identify how the performance of Lubuk Basung sub-district government in conducting the IMB application service during the post-earthquake period was performed, and what factors affected the performance. The qualitative approach-based descriptive method was used in this research. Primary data were gathered by conducting interviews with resource persons and also field direct observations. Secondary data were collected from documents and archives on the problem investigated. The resource persons involved the sub-district head and sub-district officials, and the community members who sent IMB application. This research was conducted in Lubuk Basung sub-district, Agam district. Result of the research showed that the performance of Lubuk Basung sub-district in performing the IMB services during the post-earthquake period had not been optimal based on the indicators of responsiveness, orientation to service, efficiency and accountability. The indicator responsiveness and orientation to service indicated good performance of the sub-district government. This was showed by several programs assisting the community members in terms of service and the exploitation of resources that the officials used in the service. Different from the indicators of efficiency and accountability showing the inconsistency of time and service cost, and the reference utilized in the IMB during the post-earthquake era was not able to be well implemented by the service provider and it resulted in loss for the service users. This was also affected by leadership and cooperation factors considered as having potentials to support the performance of sub-district government, and it was also internal in characteristics